Ionized and neutral gas in the XUV discs of nearby spiral galaxies. Issue Volume 10:Issue S309(2014) (9th February 2015) - López-Sánchez,; Koribalski, B. S.; Westmeier, T.; Esteban, C.
Abstract: We are conducting a multiwavelength study of XUV discs in nearby, gas-rich spiral galaxies combining the available UV (GALEX) observations with Hi data obtained at the ATCA as part of the Local Volume HI Survey (LVHIS) project and multi-object fibre spectroscopy obtained using the 2dF/AAOmega instrument at the 3.9m AAT. Here we present the results of the multiwavelength analysis of the galaxy pair NGC 1512/1510. The Hi distribution of NGC 1512 is very extended with two pronounced spiral/tidal arms. Hundreds of independent UV-bright regions are associated with dense Hi clouds in the galaxy outskirts. We confirm the detection of ionized gas in the majority of them and characterize their physical properties, chemical abundances and kinematics. Both the gas distribution andthe distribution of the star-forming regions are affected by gravitational interactionwith the neighbouring blue compact dwarf galaxy NGC 1510. Our multiwavelength analysis provides new clues about local star-formation processes, the metal redistribution in the outer gaseous discs of spiral galaxies, the importance of galaxy interactions, the fate of the neutral gas and the chemical evolution in nearby galaxies.